2008
DOI: 10.1086/522127
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of the 9 Glycoprotein Genes Found in Wild‐Type and Vaccine Strains of Varicella‐Zoster Virus

Abstract: The complete DNA sequences of wild-type and vaccine strains of varicella-zoster virus have been published and listed in GenBank. In this comparative genomic analysis, the sequences of the 9 glycoprotein open reading frames (ORFs) were compared. They included gE (ORF68), gI (ORF 67), gC (ORF14), gH (ORF37), gL (ORF60), gB (ORF31), gK (ORF5), gM (ORF50), and gN (ORF8 or ORF9A). After realignment on the basis of newer data, the corrected gB sequence was lengthened to include 931 residues. The data showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…Diminished expression of gC has been proposed as a factor related to vaccine attenuation, but it has been shown that only a single synonymous change is present in ORF14 in the vaccine 6). Our finding of downregulation of gC is consistent with that found by Kinchington et al [14] and Storlie et al [15]. gC is not necessary for replication and has variable synthesis in tissue culture, but since all three viruses had equal passages in MeWo cells is it very unlikely that the differences seen in this study are due to tissue culture passage.…”
Section: Resultssupporting
confidence: 93%
“…Diminished expression of gC has been proposed as a factor related to vaccine attenuation, but it has been shown that only a single synonymous change is present in ORF14 in the vaccine 6). Our finding of downregulation of gC is consistent with that found by Kinchington et al [14] and Storlie et al [15]. gC is not necessary for replication and has variable synthesis in tissue culture, but since all three viruses had equal passages in MeWo cells is it very unlikely that the differences seen in this study are due to tissue culture passage.…”
Section: Resultssupporting
confidence: 93%
“…20,21 The memory immune reaction, after a natural varicella, persists at a certain level of immunity protecting against VZV reinfection. Several assays have been developed to evaluate immune responses to VZV infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that VZV glycoproteins induce a strong humoral immune response following either natural infection or vaccination with the Oka strain. The SNPs in the nine VZV glycoproteins were reviewed in a recent comparative analysis (64). Some of them are specific to the vaccine strains and thus could be involved in VZV attenuation.…”
Section: Vol 82 2008 Full-length Sequencing Of Two Oka Vaccine Stramentioning
confidence: 99%